Skills in Rheumatology - Almoallim, Hani.; Cheikh, Mohamed; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2021)
This Open Access book presents practical approaches to managing patients affected by various rheumatological diseases, allowing readers to gain a better understanding of the various clinical expressions and problems experienced by these patients. Discussing rheumatology from an organ systems perspective, it highlights the importance of detailed musculoskeletal examinations when treating patients affected by rheumatological diseases. The book first explores the latest diagnostic approaches and offers key tips for accurate musculoskeletal examinations before addressing the various treatment modalities, with a particular focus on the most common joints involved in rheumatoid arthritis: the wrists and the metacarpophalangeal joints (2nd and 3rd). Featuring easy-to-understand flow diagrams and explaining the common medical problems associated with rheumatic disease, such as shortness of breath and anemia, it is not only a valuable resource to rheumatologists, but will also appeal to medical students, junior residents, and primary healthcare physicians. .
Part 1 Basics in Rheumatology -- 1 History-Taking Skills in Rheumatology -- 2 Approach to Musculoskeletal Examination -- 3 Laboratory Interpretation of Rheumatic Diseases -- 4 Pharmacotherapy in Systemic Rheumatic Diseases -- 5 Radiology in Rheumatology -- Part 2 Diagnostic approach to common medical problems in patients with rheumatic diseases -- 6 Low Back Pain -- 7 Pulmonary Manifestations of Connective Tissue Diseases -- 8 Nervous system and rheumatology -- 9 Diagnostic Approach to Proximal Myopathy -- 10 Bones and Rheumatology -- 11 Fever and Rheumatology -- 12 Thrombosis in Rheuamtological Diseases -- 13 The Blood in Rheumatology -- 14 Renal System and Rheumatology -- 15 Skin Manifestations of Rheumatological Diseases -- 16 Cardiovascular Diseases and Rheumatology -- 17 Gestational Rheumatology -- 18 Perioperative Management of Patients with Rheumatic Diseases -- 19 The Eye and Rheumatology -- 20 Vasculitisand Rheumatology -- 21 Diabetes and Rheumatology -- 22 Soft Tissue Rheumatic Disorders -- 23 Gastrointestinal System and Rheumatology -- 24 Pediatric Rheumatology -- Part 3 Classification criteria and guidelines -- 25 Classification Criteria and Clinical Practice Guidelines for Rheumatic Diseases.
Keywords: Rheumatology; Rheumatology